Correlations beCorrelations between symptoms, nasal endoscopy and computed tomography findings in patients with chronic rhinosinusitis without nasal polypstween symptoms, nasal endoscopy and computed tomography in patients with chronic rhinosinusitis - Savović, Slobodan; Dragnić, Nataša; Kljajić, Vladimir; Jovančević, Ljiljana; Buljčik-Čupić, Maja; Lemajić-Komazec, Slobodanka (Vojnosanitetski pregled, 2021)
Background/Aim. Chronic rhinosinusitis (CRS) is one of the most common chronic conditions that is diagnosed on the basis of the condition symptoms, nasal endoscopy and computed tomograhpy (CT) of the nose and paranasal sinuses. There are two forms of CRS: CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP). The aim of this paper was to determine if there is a correlation between the symptoms, nasal endoscopy and CT in patients with CRSsNP. Methods. The study included 110 patients with CRSsNP. The intensity of the symptoms assessed on the visual analogue scale (VAS) and the condition of nasal mucosa and the presence of nasal secretion was estimated by endoscopic examination of the nose while CT was used to determine the Lund-Mackay (LM) score values. Pearson’s coefficient of correlation was used for statistic data processing. Results. The severity of the disease as a whole (r = 0.509) and nasal discharge (r = 0.562) moderately correlated with CT. Nasal congestion (r = 0.354) and the reduction of loss of smell (r = 0.324) mildly correlated with CT, while facial pain/pressure (r = 0.218) had a very weak correlation with CT. The severity of the disease as a whole (r = 0.717) and nasal discharge (r = 0.821) strongly correlated with nasal endoscopy. Nasal congestion (r = 0.525) had a moderate correlation with nasal endoscopy while facial pain/pressure (r = 0.345) and the reduction of the loss of smell (r= 0.394) had a mild correlation with nasal endoscopy. A moderate correlation was found between nasal endoscopy and CT (r = 0.630). Conclusion. The severity of the disease as a whole and nasal discharge have more significant correlations both with nasal endoscopy and CT in relation to the correlations between other symptoms and nasal endoscopy, as well as CT. More significant correlations between the symptoms and nasal endoscopy in relation to the correlations between the symptoms and CT and the existence of a moderate correlation between nasal endoscopy and CT, enable a lesser use of CT diagnostics and only in precisely defined situatiations.